HUBUNGAN ANTARA PENGETAHUAN, SIKAP, DAN PERSEPSI KETERSEDIAAN APD DENGAN RISIKO KECELAKAAN KERJA PADA PEKERJA PEMADAM KEBAKARAN DI DINAS PEMADAM KEBAKARAN KOTA X - Batubara, Cindy Melita; Wahyuni, Ida; Kurniawan, Bina (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Firefighter is a job that has some fatal risks. So, both safety and health guarantees are so essential to the firefighters while doing their job in order to minimize the risk of some accidents. The purpose of this research is to give a view about X Fire Department and to find the correlation among knowledges, manner, and the perception supplies of PPE (Personal Protective Equipments) with the risks in the workspace. This research is an analytic study that use quantitative method and cross sectional approachment. The population in this case is about 100 firefighters. The sample is about 50 persons which are chosen by Simple Random Sampling method that will be analyzed with Chi-square Statistic Analysis and the instrument of this case will be using the questionnaire. in this reasearch shows that there is no correlation between Knowledge (p=0.599) and Work Risks, and there is a correlation between manner(p=0,035) and PPE Supplies (p= 0.010) to Work Risks. It should be better if we often to have some training to upgrade knowledges, manner and it is better too if the Department always have a good supply of PPE.